ANTESEDEN KEAHLIAN OPERATOR SISTEM PENGELOLAAN ASET DESA DI KABUPATEN SITUBONDO - Kustono, Alwan Sri (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2021)
Sistem Pengelolaan Aset Desa (SIPADES) is a village asset administration recording application. This application provides orderly administrative facilities for the village so that the risk of losing assets can be reduced. The purpose of this study is to test and prove various individual aspects that affect operator competence in running SIPADES. The focus of the study is on the internal factors which include anxiety and computer attitudes. Another factor tested was operator training in using SIPADES in the Situbondo District Government. The data used in this study are primary data. The technique of obtaining data using a survey method. The population that is the object of research is all of the operator of the SIPADES application in Situbondo Regency. Four hypotheses were tested using multiple regression. The gender variable was used as the control variable. The results show that all hypotheses can be accepted. The variables of anxiety, attitude, and training have an effect on the operator's competence in operating SIPADES. The implication of the research is that the village government should increase the number of SIPADES operator training. This training can increase competence to run applications.